Optical absorption by indirect excitons in a transition metal dichalcogenide/hexagonal boron nitride heterostructure. (9th May 2018) - Brunetti, Matthew N; Berman, Oleg L; Kezerashvili, Roman Ya
Abstract: We study optical transitions in spatially indirect excitons in transition metal dichalcogenide (TMDC) heterostructures separated by an integer number of hexagonal boron nitride ( h -BN) monolayers. By solving the Schrödinger equation with the Keldysh potential for a spatially indirect exciton, we obtain eigenfunctions and eigenenergies for the ground and excited states and study their dependence on the interlayer separation, controlled by varying the number of h -BN monolayers. The oscillator strength, optical absorption coefficient, and optical absorption factor, the fraction of incoming photons absorbed in the TMDC/ h -BN/TMDC heterostructure, are evaluated and studied as a function of the interlayer separation. Using input parameters from the existing literature which give the largest and the smallest spatially indirect exciton binding energy, we provide upper and lower bounds on all quantities presented.